Composite positive electrode material, positive electrode plate and battery

By using lithium manganese oxide materials and lithium-rich sodium-rich manganese-based materials in composite positive electrode materials, and controlling their particle size difference and mass fraction, the performance limitations of spinel lithium manganese in the power field are solved, achieving high Compact density and excellent cycling performance.

CN119400847AActive Publication Date: 2025-02-07NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202510013073.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-07
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The application of spinel lithium manganate in the power field is limited by its low energy density, severe manganese dissolution during circulation and Jahn-Teller effect, and lithium-rich manganese-based materials are costly and have poor structural stability.

Method used

Using a composite positive electrode material, including lithium manganese oxide material and lithium-rich sodium-rich manganese-based material, by controlling the particle size difference and mass fraction of the two, ensure that the median particle size of lithium manganese-based material is greater than that of lithium-rich sodium-rich Manganese-based material and coordinated control of compaction density in composite materials.

Benefits of technology

The compaction density of the composite positive electrode material is significantly improved, the capacity attenuation problem of lithium manganese oxide material in the early stage of circulation is overcome, the first Coulomb efficiency and discharge capacity are improved, and the structural stability and cycling performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400847A_ABST
    Figure CN119400847A_ABST
Patent Text Reader

Abstract

The invention relates to a composite positive electrode material, a positive electrode plate and a battery. The composite positive electrode material comprises a lithium manganate material and a lithium-rich sodium-rich manganese-based material, and the median particle size of the lithium manganate material is greater than that of the lithium-rich sodium-rich manganese-based material; the compaction density PD of the composite positive electrode material meets 1.05 * (X1 * PD1 + X2 * PD2) lt; pDlt; 1.2 * (X1 * PD1 + X2 * PD2), and PDgt; x1 represents the mass fraction of the lithium manganate material in the composite positive electrode material, X1 is larger than or equal to 50% and smaller than or equal to 90%, PD1 represents the compaction density of the lithium manganate material, X2 represents the mass fraction of the lithium-rich sodium-rich manganese-based material in the composite positive electrode material, X2 is larger than or equal to 10% and smaller than or equal to 50%, PD2 represents the compaction density of the lithium-rich sodium-rich manganese-based material, and max represents the maximum value of PD1 and PD2. The composite positive electrode material disclosed by the invention is lower in cost and excellent in cycle performance, and can remarkably improve the electrical performance when being applied to a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and particularly to a composite cathode material, a cathode pole piece and a battery. Background Art

[0002] Spinel lithium manganate has a three-dimensional diffusion channel for lithium ions, excellent rate performance and low-temperature performance, and low cost, and has received extensive attention in recent years. However, its relatively low energy density and serious manganese dissolution and Jahn-Teller effect during cycling greatly limit its application in the power field.

[0003] Although the performance defects of lithium manganate can be compensated by blending spinel lithium manganate with lithium-rich manganese-based materials, the cost of lithium-rich manganese-based materials is relatively high, and there are phenomena of oxygen release and transformation from layered structure to spinel structure and then to rock salt structure during cycling, resulting in poor structural stability and cycling performance of the blended cathode material. Therefore, it is urgent to develop a cathode material with both low cost and high cycling performance. Summary of the Invention

[0004] Based on this, it is necessary to provide a composite cathode material, a cathode pole piece and a battery for the above problems; the composite cathode material not only has a lower cost, but also has excellent cycling performance, and can significantly improve the electrical performance when applied to a battery.

[0005] A composite cathode material includes a lithium manganate material and a lithium-rich and sodium-rich manganese-based material, and the median particle size of the lithium manganate material is greater than the median particle size of the lithium-rich and sodium-rich manganese-based material; The tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2) < PD < 1.2×(X1×PD1 + X2×PD2), and PD > 1.02×max{PD1, PD2}, where X1 represents the mass fraction of the lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 90%, PD1 represents the tap density of the lithium manganate material, X2 represents the mass fraction of the lithium-rich and sodium-rich manganese-based material in the composite cathode material, 10% ≤ X2 ≤ 50%, PD2 represents the tap density of the lithium-rich and sodium-rich manganese-based material, and max represents taking the maximum value of PD1 and PD2.

[0006] In one embodiment, the particle size distribution width SPAN of the composite cathode material satisfies: SPAN ≥ 1.3×(SPAN1 + SPAN2) / 2, where SPAN1 represents the particle size distribution width of the lithium manganate material, and SPAN2 represents the particle size distribution width of the lithium-rich and sodium-rich manganese-based material.

[0007] In one embodiment, the difference between the median particle size of the lithium manganate material and the median particle size of the lithium-rich and sodium-rich manganese-based material is 5 μm - 15 μm.

[0008] In one embodiment, the lithium manganate material satisfies at least one of the following conditions: (1) 8 μm ≤ D 50 ≤ 20 μm; (2) 3 μm ≤ D 10 ≤ 7 μm; (3) The particle size distribution width SPAN1 of the lithium manganate material is 1 - 2; (4) The tap density PD1 of the lithium manganate material is 2.6 g / cm 3 - 2.9 g / cm 3 ; (5) The specific surface area of the lithium manganate material is 0.2 m 2 / g - 0.8 m 2 / g; (6) The lithium manganate material has a spinel crystal structure; (7) The chemical formula of the lithium manganate material is Li 1+x Mn 2-a A a O4D b , where 0 ≤ x ≤ 0.2, 0 < a ≤ 0.2, 0 ≤ b ≤ 0.05, A represents a cation doping element, A is selected from at least one of W, Mo, V, Ta, Nb, P, Zr, Ti, Cr, Al, Fe, La, Ce, Nd, Sm, Gd, Tm, Bi, Co, Mg, Ni, Zn, and D represents an anion doping element, D is selected from at least one of F, Cl, I, S.

[0009] In one embodiment, the lithium-rich and sodium-rich manganese-based material satisfies at least one of the following conditions: (1) 3 μm ≤ D 50 ≤ 6 μm; (2) 1 μm ≤ D 10 ≤ 4 μm; (3) The particle size distribution width SPAN2 of the lithium-rich and sodium-rich manganese-based material is 0.5 - 1.5; (4) The tap density PD2 of the lithium-rich and sodium-rich manganese-based material is 2.7 g / cm 3 - 2.9 g / cm 3 ; (5) The specific surface area of the lithium-rich and sodium-rich manganese-based material is 1 m 2 / g - 4 m 2 / g; (6) The lithium-rich and sodium-rich manganese-based material has a layered structure; (7) In the X-ray diffraction pattern of the lithium-rich and sodium-rich manganese-based material, the diffraction peak intensities of (002), (003), (104), and (101) are respectively denoted as I(002) 、I (003) 、I (104) 、I (101) ,0.01 ≤ I (002) / [I (003) + I (104) + I (101) ≤ 0.5; (8)The chemical formula of the lithium-rich and sodium-rich manganese-based material is Li 1+m Na n Ni 1-c-d-e Co c Mn d M e O f E g E, where 0 ≤ m ≤ 0.3, 0.05 ≤ n ≤ 0.3, and 0.1 ≤ m + n ≤ 0.5, 0.2 ≤ 1 - c - d - e ≤ 0.4, 0 ≤ c ≤ 0.1, 0.5 ≤ d ≤ 0.8, 0 < e ≤ 0.05, 0 ≤ g ≤ 0.1, and f + g = 2 + m + n. M represents a cation doping element, and M is selected from at least one of W, Mo, Nb, Ta, V, Te, Sb, Ce, Ti, Zr, Sn, B, Cr, Fe, Al, La, Sc, Sm, Y, Ba, Mg, Sr, Zn, Cu, K. E represents an anion doping element, and E is selected from at least one of F, Cl, I, S.

[0010] In one embodiment, the composite cathode material further includes lithium iron manganese phosphate material, and the median particle size of the lithium-rich and sodium-rich manganese-based material is greater than that of the lithium iron manganese phosphate material; The tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2 + X3×PD3) < PD < 1.2×(X1×PD1 + X2×PD2 + X3×PD3), and PD > 1.02×max{PD1, PD2, PD3}, where X1 represents the mass fraction of lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 70%, PD1 represents the tap density of lithium manganate material, X2 represents the mass fraction of the lithium-rich and sodium-rich manganese-based material in the composite cathode material, 20% ≤ X2 ≤ 40%, PD2 represents the tap density of the lithium-rich and sodium-rich manganese-based material, X3 represents the mass fraction of lithium iron manganese phosphate material in the composite cathode material, 5% ≤ X3 ≤ 20%, PD3 represents the tap density of lithium iron manganese phosphate material, and max represents taking the maximum value of PD1, PD2, and PD3.

[0011] In one embodiment, the particle size distribution width SPAN of the composite cathode material satisfies SPAN≥1.3×(SPAN1 + SPAN2 + SPAN3) / 3, where SPAN1 represents the particle size distribution width of the lithium manganate material, SPAN2 represents the particle size distribution width of the lithium-rich and sodium-rich manganese-based material, and SPAN3 represents the particle size distribution width of the lithium iron manganese phosphate material.

[0012] In one embodiment, the difference between the median particle size of the lithium-rich and sodium-rich manganese-based material and the median particle size of the lithium iron manganese phosphate material is 2 μm - 5 μm.

[0013] In one embodiment, the lithium iron manganese phosphate material satisfies at least one of the following conditions: (1) 0.5 μm ≤ D 50 ≤ 2 μm; (2) 0.1 μm ≤ D 10 ≤ 1 μm; (3) The particle size distribution width SPAN3 of the lithium iron manganese phosphate material is 1.0 - 3.0; (4) The tap density PD3 of the lithium iron manganese phosphate material is 2.0 g / cm 3 - 2.5 g / cm 3 ; (5) The specific surface area of the lithium iron manganese phosphate material is 15 m 2 / g - 25 m 2 / g; (6) The lithium iron manganese phosphate material has an olivine crystal structure; (7) The chemical formula of the lithium iron manganese phosphate material is Li 1+y Mn p Fe q Q 1-p-q PO4@C, where 0 ≤ y ≤ 0.1, 0.4 ≤ p < 1, 0 < q ≤ 0.6, 0 ≤ 1 - p - q ≤ 0.05, and Q is selected from at least one of V, Nb, Ti, Zr, Al, Mg, Ni, Co, Zn.

[0014] In one embodiment, the composite cathode material satisfies at least one of the following conditions: (1) 3 μm ≤ D 50 ≤ 15 μm; (2) 1 μm ≤ D 10 ≤ 4 μm; (3) The particle size distribution width SPAN of the composite cathode material is ≥ 2.0; (4) The tap density PD of the composite cathode material is ≥ 2.9 g / cm 3 ; (5) The specific surface area of the composite cathode material is 0.5 m 2 / g-6m 2 / g.

[0015] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the composite positive electrode material as described above.

[0016] A battery comprises the positive electrode sheet as described above.

[0017] The composite positive electrode material described in the present invention adopts a low-cost lithium-rich and sodium-rich manganese-based material. By mixing a lithium manganate material with a larger particle size with a lithium-rich and sodium-rich manganese-based material with a smaller particle size, and synergistically controlling the mass fraction and particle size difference of the lithium manganate material and the lithium-rich and sodium-rich manganese-based material, not only the compaction is greatly improved, but also the capacity attenuation problem of the lithium manganate material in the early stage of the cycle is overcome, and the first coulombic efficiency and discharge capacity of the composite positive electrode material are improved. Moreover, compared with the lithium-rich manganese-based material at the same mixing ratio, the composite positive electrode material mixed with the lithium-rich and sodium-rich manganese-based material provided by the present invention has better structural stability, which is beneficial to improving the cycle performance. Therefore, applying it to the battery can significantly improve the electrical performance, especially the cycle performance and rate performance, thereby improving the fast charging performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope (SEM) image of the lithium manganate material prepared in Example 1; Figure 2 This is a scanning electron microscope (SEM) image of the lithium-rich and sodium-rich manganese-based material prepared in Example 1; Figure 3 This is an X-ray diffraction (XRD) diagram of the lithium-rich and sodium-rich manganese-based material obtained in Example 1, wherein △ represents a characteristic peak of the P2 phase; Figure 4 This is a scanning electron microscope (SEM) image of the composite positive electrode material prepared in Example 1; Figure 5 This is a particle size distribution diagram of the composite positive electrode material prepared in Example 1; Figure 6 This is a scanning electron microscope (SEM) image of a mixture of the lithium manganate material and the lithium iron manganese phosphate material obtained in Example 9; Figure 7 This is a scanning electron microscope (SEM) image of the composite positive electrode material prepared in Example 9; Figure 8 This is the particle size distribution diagram of the composite positive electrode material prepared in Example 9. DETAILED DESCRIPTION

[0019] To facilitate the understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, these embodiments or examples are provided to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the description of the present invention herein are only for the purpose of describing specific embodiments or examples and are not intended to limit the present invention.

[0021] The present invention provides a composite cathode material, including lithium manganate material and lithium-rich and sodium-rich manganese-based material, and the median particle size of the lithium manganate material is greater than that of the lithium-rich and sodium-rich manganese-based material.

[0022] The tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2) < PD < 1.2×(X1×PD1 + X2×PD2), and PD > 1.02×max{PD1, PD2}. Preferably, PD > 1.03×max{PD1, PD2}; more preferably, PD > 1.04×max{PD1, PD2}. Wherein, X1 represents the mass fraction of the lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 90%, PD1 represents the tap density of the lithium manganate material, X2 represents the mass fraction of the lithium-rich and sodium-rich manganese-based material in the composite cathode material, 10% ≤ X2 ≤ 50%, PD2 represents the tap density of the lithium-rich and sodium-rich manganese-based material, and max represents taking the maximum value of PD1 and PD2.

[0023] The present invention mixes the larger-particle-size lithium manganate material with the smaller-particle-size lithium-rich and sodium-rich manganese-based material and controls the mass fractions of the lithium manganate material and the lithium-rich and sodium-rich manganese-based material, so that the tap density of the composite cathode material is greatly improved. In addition, the lithium-rich and sodium-rich manganese-based material adopted in the present invention has a P2-O3 type composite structure, and the two phases are evenly distributed, and the P2 phase is occupied by sodium ions and vacancies. During the charging process, some sodium ions will be removed and participate in the formation of the negative electrode SEI film, which is beneficial to reducing the loss of active lithium. This not only overcomes the problem of capacity decay of the lithium manganate material in the initial stage of cycling, improves the first Coulomb efficiency and discharge capacity of the composite cathode material, but also has better structural stability of the composite cathode material doped with the lithium-rich and sodium-rich manganese-based material compared with the lithium-rich manganese-based material under the same mixing ratio, which is beneficial to improving the cycling performance and has lower cost.

[0024] Specifically, the mass fraction X1 of the lithium manganese oxide material in the composite positive electrode material includes but is not limited to any point value among 50%, 60%, 70%, 80%, 90% or a range value between any two of them; the mass fraction X2 of the lithium-rich and sodium-rich manganese-based material in the composite positive electrode material includes but is not limited to any point value among 10%, 20%, 30%, 40%, 50% or a range value between any two of them.

[0025] In one embodiment, the particle size distribution width SPAN of the composite positive electrode material is ≥1.3×(SPAN1+SPAN2) / 2, wherein SPAN1 represents the particle size distribution width of the lithium manganese oxide material, and SPAN2 represents the particle size distribution width of the lithium-rich and sodium-rich manganese-based material.

[0026] It can be understood that the particle size distribution width SPAN = (D 90 -D 10 ) / D 50 , where D 50 It is the particle size corresponding to the particle volume accumulation of 50%, that is, the median particle size; D 90 D is the particle size corresponding to when the particle volume accumulates to 90%; 10 It is the particle size corresponding to when the particle volume accumulates to 10%.

[0027] In one embodiment, the difference between the median particle size of the lithium manganate material and the median particle size of the lithium-rich sodium-rich manganese-based material is 5μm-15μm, including but not limited to any point value of 5μm, 8μm, 10μm, 12μm, 15μm or any range value between the two. It is further preferably 6μm-15μm, including but not limited to any point value of 6μm, 8μm, 10μm, 12μm, 15μm or any range value between the two. It is further preferably 6μm-12μm, including but not limited to any point value of 6μm, 8μm, 10μm, 12μm or any range value between the two.

[0028] In one embodiment, the median particle size of the lithium manganate material is preferably 8 μm-20 μm, including but not limited to any point value of 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or any range value between two thereof. It is further preferably 9 μm-18 μm, including but not limited to any point value of 9 μm, 10 μm, 12 μm, 15 μm, 18 μm or any range value between two thereof. It is further preferably 10 μm-18 μm, including but not limited to any point value of 10 μm, 12 μm, 15 μm, 18 μm or any range value between two thereof.

[0029] In one embodiment, D of the lithium manganate material 10Preferably, it is 3 μm-7 μm, including but not limited to any point value among 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or any range value between two thereof. More preferably, it is 3 μm-6 μm, including but not limited to any point value among 3 μm, 4 μm, 5 μm, 6 μm or any range value between two thereof.

[0030] In one embodiment, the particle size distribution width SPAN1 of the lithium manganate material is preferably 1-2, including but not limited to any point value among 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any range value between two thereof. It is further preferably 1.2-2, including but not limited to any point value among 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any range value between two thereof.

[0031] In one embodiment, the compacted density PD1 of the lithium manganate material is preferably 2.6 g / cm 3 -2.9g / cm 3 , including but not limited to 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 Any point value in or any range of values ​​between them.

[0032] In one embodiment, the specific surface area of ​​the lithium manganate material is preferably 0.2 m 2 / g-0.8m 2 / g, including but not limited to 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 / g or any range between them. More preferably, 0.3m 2 / g-0.8m 2 / g, including but not limited to 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 Any point value in / g or any range of values ​​between them.

[0033] In one embodiment, the lithium manganese oxide material has a spinel crystal structure.

[0034] In one embodiment, the chemical formula of the lithium manganese oxide material is Li1+x Mn 2-a A a O4D b , wherein 0 ≤ x ≤ 0.2, 0 < a ≤ 0.2, 0 ≤ b ≤ 0.05. Preferably, 0.01 ≤ x ≤ 0.15, 0.001 ≤ a ≤ 0.18, 0.001 ≤ b ≤ 0.045. More preferably, 0.02 ≤ x ≤ 0.12, 0.002 ≤ a ≤ 0.15, 0.002 ≤ b ≤ 0.04; A represents a cationic doping element, and A is selected from at least one of W, Mo, V, Ta, Nb, P, Zr, Ti, Cr, Al, Fe, La, Ce, Nd, Sm, Gd, Tm, Bi, Co, Mg, Ni, Zn. Preferably, A is selected from at least one of Nb, P, Cr, Al, La, Sm, Gd, Co, Mg, Ni; D represents an anionic doping element, and D is selected from at least one of F, Cl, I, S. Preferably, D is selected from at least one of F, Cl, I. More preferably, D is selected from at least one of F, Cl. Even more preferably, D is selected from F.

[0035] In one embodiment, the median particle size of the lithium-rich and sodium-rich manganese-based material is preferably 3 μm - 6 μm, including but not limited to any value among 3 μm, 4 μm, 5 μm, 6 μm or the range values between any two of them. More preferably, it is 3 μm - 5 μm, including but not limited to any value among 3 μm, 4 μm, 5 μm or the range values between any two of them.

[0036] In one embodiment, the D of the lithium-rich and sodium-rich manganese-based material 10 is preferably 1 μm - 4 μm, including but not limited to any value among 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or the range values between any two of them. More preferably, it is 1.5 μm - 3.5 μm, including but not limited to any value among 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or the range values between any two of them. Even more preferably, it is 2 μm - 3.5 μm, including but not limited to any value among 2 μm, 2.5 μm, 3 μm, 3.5 μm or the range values between any two of them.

[0037] In one embodiment, the particle size distribution width SPAN2 of the lithium-rich and sodium-rich manganese-based material is preferably 0.5 - 1.5, including but not limited to any value among 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or the range values between any two of them. More preferably, it is 0.6 - 1.2, including but not limited to any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or the range values between any two of them.

[0038] In one embodiment, the compaction density PD2 of the lithium-rich sodium-rich manganese-based material is preferably 2.7 g / cm 3 -2.9g / cm 3 , including but not limited to 2.7g / cm 3 , 2.75g / cm 3 , 2.8g / cm 3 , 2.85g / cm 3 , 2.9g / cm 3 Any point value in or any range of values ​​between them.

[0039] In one embodiment, the specific surface area of ​​the lithium-rich sodium-rich manganese-based material is preferably 1 m 2 / g-4m 2 / g, including but not limited to 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 Any point value in / g or any range of values ​​between them.

[0040] In one embodiment, the lithium-rich and sodium-rich manganese-based material has a layered structure.

[0041] In one embodiment, in the X-ray diffraction pattern of the lithium-rich sodium-rich manganese-based material, the diffraction peak intensities of (002), (003), (104), and (101) are respectively denoted as I (002) ,I (003) ,I (104) ,I (101) , 0.01≤I (002) / [I (003) +I (104) +I (101) ]≤0.5, preferably, 0.02≤I (002) / [I (003) +I (104) +I (101) ]≤0.4, more preferably, 0.05≤I (002) / [I (003) +I (104) +I (101) ]≤0.2. It should be noted that (002) represents the diffraction peak of the P2 phase, and (003), (104) and (101) represent the three strong diffraction peaks of the O3 phase. By adjusting the proportion of the P2 phase in the lithium-rich and sodium-rich manganese-based material, it is beneficial to reduce the residual alkali of the material, further improve the structural stability and dynamic performance, and thus improve the cycle performance.

[0042] In one embodiment, the chemical formula of the lithium-rich sodium-rich manganese-based material is Li 1+m Na n Ni1-c-d-e Co c Mn d M e O f E g where 0 ≤ m ≤ 0.3, 0.05 ≤ n ≤ 0.3, and 0.1 ≤ m + n ≤ 0.5, 0.2 ≤ 1 - c - d - e ≤ 0.4, 0 ≤ c ≤ 0.1, 0.5 ≤ d ≤ 0.8, 0 < e ≤ 0.05, 0 ≤ g ≤ 0.1, and f + g = 2 + m + n. Preferably, 0.1 ≤ m ≤ 0.3, 0.05 ≤ n ≤ 0.25, 0.15 ≤ m + n ≤ 0.5, 0.25 ≤ 1 - c - d - e ≤ 0.4, 0.005 ≤ c ≤ 0.09, 0.6 ≤ d ≤ 0.8, 0.001 ≤ e ≤ 0.05, 0.005 ≤ g ≤ 0.08. More preferably, 0.15 ≤ m ≤ 0.3, 0.05 ≤ n ≤ 0.2, 0.2 ≤ m + n ≤ 0.5, 0.25 ≤ 1 - c - d - e ≤ 0.35, 0.005 ≤ c ≤ 0.08, 0.6 ≤ d ≤ 0.7, 0.002 ≤ e ≤ 0.04, 0.005 ≤ g ≤ 0.05; M represents a cationic doping element, and M is selected from at least one of W, Mo, Nb, Ta, V, Te, Sb, Ce, Ti, Zr, Sn, B, Cr, Fe, Al, La, Sc, Sm, Y, Ba, Mg, Sr, Zn, Cu, K. Preferably, M is selected from at least one of W, Mo, Nb, Te, Sb, Ti, Cr, Al. More preferably, M is selected from at least one of W, Nb, Ti; E represents an anionic doping element, and E is selected from at least one of F, Cl, I, S. Preferably, E is selected from at least one of F, Cl, I. More preferably, E is selected from at least one of F, Cl.

[0043] In one embodiment, the composite cathode material further includes lithium iron manganese phosphate material, and the median particle size of the lithium-rich and sodium-rich manganese-based material is greater than the median particle size of the lithium iron manganese phosphate material.

[0044] When the composite cathode material includes lithium manganate material, lithium-rich and sodium-rich manganese-based material, and lithium iron phosphate manganese material, the tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2 + X3×PD3) < PD < 1.2×(X1×PD1 + X2×PD2 + X3×PD3), and PD > 1.02×max{PD1, PD2, PD3}. Preferably, PD > 1.03×max{PD1, PD2, PD3}; more preferably, PD > 1.04×max{PD1, PD2, PD3}. Wherein, X1 represents the mass fraction of lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 70%, PD1 represents the tap density of lithium manganate material, X2 represents the mass fraction of lithium-rich and sodium-rich manganese-based material in the composite cathode material, 20% ≤ X2 ≤ 40%, PD2 represents the tap density of lithium-rich and sodium-rich manganese-based material, X3 represents the mass fraction of lithium iron phosphate manganese material in the composite cathode material, 5% ≤ X3 ≤ 20%, PD3 represents the tap density of lithium iron phosphate manganese material, and max represents taking the maximum value among PD1, PD2, and PD3.

[0045] In the present invention, by blending lithium manganate material, lithium-rich and sodium-rich manganese-based material, and lithium iron phosphate manganese material, the lithium iron phosphate manganese material with the smallest particle size can coat the surface of the lithium manganate material and / or the lithium-rich and sodium-rich manganese-based material, greatly improving the electrochemical performance, especially the cycling performance of the composite cathode material. In addition, by controlling the mass fractions and particle size differences of the lithium manganate material, the lithium-rich and sodium-rich manganese-based material, and the lithium iron phosphate manganese material, the tap density of the composite cathode material can also be greatly increased, significantly improving the battery energy density.

[0046] Specifically, the mass fraction X1 of lithium manganate material in the composite cathode material includes but is not limited to any point value or the range value between any two of 50%, 55%, 60%, 65%, and 70%; the mass fraction X2 of lithium-rich and sodium-rich manganese-based material in the composite cathode material includes but is not limited to any point value or the range value between any two of 20%, 25%, 30%, 35%, and 40%; the mass fraction X3 of lithium iron phosphate manganese material in the composite cathode material includes but is not limited to any point value or the range value between any two of 5%, 10%, 15%, and 20%.

[0047] In an embodiment, the particle size distribution width SPAN of the composite cathode material ≥ 1.3×(SPAN1 + SPAN2 + SPAN3) / 3, where SPAN1 represents the particle size distribution width of lithium manganate material, SPAN2 represents the particle size distribution width of lithium-rich and sodium-rich manganese-based material, and SPAN3 represents the particle size distribution width of lithium iron phosphate manganese material.

[0048] In one embodiment, the difference between the median particle size of the lithium-rich and sodium-rich manganese-based material and the median particle size of the lithium iron manganese phosphate material is 2μm-5μm, including but not limited to any point value of 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 5μm or any range value between two of them.

[0049] In one embodiment, the median particle size of the lithium manganese iron phosphate material is preferably 0.5 μm-2 μm, including but not limited to any point value of 0.5 μm, 1 μm, 1.5 μm, 2 μm, or a range between any two of them. It is further preferably 0.5 μm-1.5 μm, including but not limited to any point value of 0.5 μm, 1 μm, 1.5 μm, or a range between any two of them.

[0050] In one embodiment, D of the lithium manganese iron phosphate material 10 Preferably, it is 0.1 μm-1 μm, including but not limited to any point value among 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, or any range value between two thereof. More preferably, it is 0.1 μm-0.8 μm, including but not limited to any point value among 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or any range value between two thereof. More preferably, it is 0.1 μm-0.6 μm, including but not limited to any point value among 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, or any range value between two thereof.

[0051] In one embodiment, the particle size distribution width SPAN3 of the lithium manganese iron phosphate material is preferably 1.0-3.0, including but not limited to any point value of 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or any range between two values. It is further preferably 1.2-2.8, including but not limited to any point value of 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or any range between two values.

[0052] In one embodiment, the compaction density PD3 of the lithium manganese iron phosphate material is preferably 2.0 g / cm 3 -2.5g / cm 3 , including but not limited to 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 Any point value in or any range value between two values. More preferably, 2.1 g / cm 3 -2.5g / cm 3 , including but not limited to 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 Any point value in or any range of values ​​between them.

[0053] In one embodiment, the specific surface area of ​​the lithium manganese iron phosphate material is preferably 15 m 2 / g-25m 2 / g, including but not limited to 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g or any point value or any range value between the two. More preferably, 16m 2 / g-24m 2 / g, including but not limited to 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g or any point value or any range value between the two. More preferably, 16m 2 / g-22m 2 / g, including but not limited to 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m2 Any point value in / g or a range value between any two of them.

[0054] In one embodiment, the lithium iron manganese phosphate material has an olivine crystal structure.

[0055] In one embodiment, the chemical formula of the lithium iron manganese phosphate material is Li 1+y Mn p Fe q Q 1-p-q PO4@C, where 0 ≤ y ≤ 0.1, 0.4 ≤ p < 1, 0 < q ≤ 0.6, 0 ≤ 1 - p - q ≤ 0.05. Preferably, 0 ≤ y ≤ 0.08, 0.6 ≤ p ≤ 0.8, 0.2 ≤ q ≤ 0.4, 0 ≤ 1 - p - q ≤ 0.04. Further preferably, 0.01 ≤ y ≤ 0.06, 0.6 ≤ p ≤ 0.7, 0.2 ≤ q ≤ 0.3, 0.001 ≤ 1 - p - q ≤ 0.03; Q is selected from at least one of V, Nb, Ti, Zr, Al, Mg, Ni, Co, Zn. Preferably, Q is selected from at least one of Ti, Mg, Ni, Co, Zn. It should be noted that @C represents carbon-coated lithium iron manganese phosphate, and the mass fraction of carbon in the lithium iron manganese phosphate is 1% - 3%. Preferably, the mass fraction of carbon in the lithium iron manganese phosphate is 1% - 2%.

[0056] In one embodiment, the median particle size of the composite cathode material is preferably 3 μm - 15 μm, including but not limited to any point value in 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, 14 μm, 15 μm or a range value between any two of them.

[0057] In one embodiment, the D 10 of the composite cathode material is preferably 1 μm - 4 μm, including but not limited to any point value in 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or a range value between any two of them. Further preferably, it is 1 μm - 3 μm, including but not limited to any point value in 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or a range value between any two of them.

[0058] In one embodiment, the particle size distribution width of the composite cathode material preferably has SPAN ≥ 2.0, further preferably SPAN ≥ 2.2, and more preferably SPAN ≥ 2.5.

[0059] In one embodiment, the tap density PD of the composite cathode material is preferably ≥ 2.9 g / cm 3 , further preferably ≥ 3.0 g / cm 3 .

[0060] In one embodiment, the specific surface area of ​​the composite positive electrode material is preferably 0.5 m 2 / g-6m 2 / g, more preferably 0.6m 2 / g-5m 2 / g, more preferably 0.6m 2 / g-4m 2 / g.

[0061] In one embodiment, the composite positive electrode material is a spherical structure, which is formed by aggregation of secondary particles, and the secondary particles are composed of primary particles and / or primary layers. Specifically, when the composite positive electrode material includes lithium manganese oxide material, lithium-rich and sodium-rich manganese-based material and lithium iron manganese phosphate material, at least part of the lithium iron manganese phosphate material is coated on the surface of the lithium manganese oxide material and / or the lithium-rich and sodium-rich manganese-based material, and part of the lithium iron manganese phosphate material is filled in the gaps between adjacent large particles.

[0062] In one embodiment, in the electrochemical window of 3.00V-4.35V, the composite positive electrode material has a room temperature half-charge 0.1C discharge capacity of ≥123mAh / g, a first efficiency of ≥94%, a 2C discharge capacity of ≥113mAh / g, a 3C discharge capacity of ≥108mAh / g, and (3C discharge capacity / 0.1C discharge capacity×100)%≥85%. Preferably, in the electrochemical window of 3.00V-4.35V, the composite positive electrode material has a room temperature half-charge 0.1C discharge capacity of ≥124mAh / g, a first efficiency of ≥94%, a 2C discharge capacity of ≥114mAh / g, a 3C discharge capacity of ≥109mAh / g, and (3C discharge capacity / 0.1C discharge capacity×100)%≥85%. Further preferably, in the electrochemical window of 3.00V-4.35V, the 0.1C discharge capacity of the composite positive electrode material at room temperature after half-charge is ≥125mAh / g, the first efficiency is ≥95%, the 2C discharge capacity is ≥115mAh / g, the 3C discharge capacity is ≥110mAh / g, and (3C discharge capacity / 0.1C discharge capacity×100)% is ≥85%.

[0063] In one embodiment, under the electrochemical window of 2.95V-4.30V, the capacity retention rate of the composite positive electrode material soft pack after 100 cycles of full-electric high temperature (45°C) 1C cycle is ≥92%. Preferably, under the electrochemical window of 2.95V-4.30V, the capacity retention rate of the composite positive electrode material soft pack after 100 cycles of full-electric high temperature (45°C) 1C cycle is ≥93%. Further preferably, under the electrochemical window of 2.95V-4.30V, the capacity retention rate of the composite positive electrode material soft pack after 100 cycles of full-electric high temperature (45°C) 1C cycle is ≥94%.

[0064] It should be noted that the present invention does not limit the specific preparation method of the composite positive electrode material. The lithium manganate material can be mixed with the lithium-rich sodium-rich manganese-based material to prepare the composite positive electrode material, or the lithium manganate material can be mixed with the lithium iron manganese phosphate material and then mixed with the lithium-rich sodium-rich manganese-based material to prepare the composite positive electrode material. It can be understood that the present invention does not limit the specific preparation method of the lithium manganate material, the lithium iron manganese phosphate material and the lithium-rich sodium-rich manganese-based material, and the existing preparation process can be used.

[0065] In one embodiment, it is preferred to mix a lithium manganese oxide material with a lithium-rich and sodium-rich manganese-based material to obtain a composite positive electrode material. For example, a lithium source, a manganese source and a cationic additive are mixed, and the lithium manganese oxide material is obtained by sintering, cooling, crushing and screening; a lithium source, a sodium source, a manganese-based precursor and a cationic additive are mixed, and the lithium-rich and sodium-rich manganese-based material is obtained by sintering, cooling, crushing and screening, washing and drying; the obtained lithium manganese oxide material is mixed with a lithium-rich and sodium-rich manganese-based material to obtain a composite positive electrode material.

[0066] In another embodiment, the lithium source, manganese source and cationic additive are preferably mixed, and a lithium manganese oxide material is obtained by sintering, cooling, crushing and screening; the lithium source, manganese source, iron source, phosphate, additive, carbon source and deionized water are mixed and ground, and then spray-dried, sintered, cooled, crushed and screened to obtain a lithium iron manganese phosphate material; the prepared lithium manganese oxide material is mixed with the lithium iron manganese phosphate material to obtain a mixture; the lithium source, sodium source, manganese-based precursor and cationic additive are mixed, and a lithium-rich sodium-rich manganese-based material is obtained by sintering, cooling, crushing, screening, washing and drying; the prepared mixture is mixed with a lithium-rich sodium-rich manganese-based material to obtain a composite positive electrode material.

[0067] By first mixing the large-particle lithium manganese oxide material with the small-particle lithium iron manganese phosphate material, it is beneficial to improve the coating effect of the lithium iron manganese phosphate material on the lithium manganese oxide material, and then mixing it with the medium-particle lithium-rich sodium-rich manganese-based material to make part of the lithium iron manganese phosphate material fill the gaps between the particles, which can not only significantly improve the electrochemical properties of the composite positive electrode material, but also help to further improve the compaction density of the composite positive electrode material.

[0068] It is understandable that the lithium iron manganese phosphate material can also be mixed with the lithium manganese oxide material and the lithium-rich sodium-rich manganese-based material to form two mixtures, and then the two mixtures are mixed to form a composite positive electrode material, so that the surfaces of the lithium manganese oxide material and the lithium-rich sodium-rich manganese-based material are coated with the lithium iron manganese phosphate material, and the present invention will not go into details about this.

[0069] Specifically, in the step of preparing the lithium manganate material, the lithium source is selected from at least one of Li2CO3, LiOH, LiOH·H2O, LiNO3, and Li2SO4, the manganese source is preferably (quasi) spherical Mn3O4, the cationic additive is selected from at least one of an oxide containing the G element, a hydroxide containing the G element, a phosphate containing the G element, a carbonate containing the G element, a chloride containing the G element, a fluoride containing the G element, an iodide containing the G element, and a sulfide containing the G element, the G element is selected from at least one of W, Mo, V, Ta, Nb, P, Zr, Ti, Cr, Al, Fe, La, Ce, Nd, Sm, Gd, Tm, Bi, Co, Mg, Ni, and Zn, and the anionic additive can be selected from at least one of the above-mentioned chlorides, fluorides, iodides, and sulfides containing the G element, and can also be selected from at least one of lithium salts containing F, Cl, I, and S.

[0070] The sintering process is preferably: heating to a pre-firing temperature of 450°C-650°C at 1°C / min-15°C / min, keeping warm for 2h-10h, then heating to a sintering temperature of 650°C-900°C, keeping warm for 6h-20h, then cooling to an annealing temperature of 500°C-700°C at 0.2°C / min-5°C / min, keeping warm for less than 8h, and finally cooling naturally.

[0071] Specifically, in the step of preparing the lithium-rich and sodium-rich manganese-based material, the lithium source is selected from at least one of Li2CO3, LiOH, LiOH·H2O, LiNO3, and Li2SO4, the sodium source is selected from at least one of Na2CO3, NaOH, Na2SO4, and Na2C2O4, and the manganese-based precursor is selected from Ni a Co b Mn c (OH)2、Ni a Co b Mn c CO3、Ni a Co b Mn cAt least one of O, where 0.25 < a ≤ 0.35, 0.005 ≤ b ≤ 0.08, 0.6 ≤ c < 0.7, and a + b + c = 1. The cationic additive is selected from at least one of an oxide containing element J, a hydroxide containing element J, a phosphate containing element J, a carbonate containing element J, a chloride containing element J, a fluoride containing element J, an iodide containing element J, and a sulfide containing element J. Element J is selected from at least one of W, Mo, Nb, Ta, V, Te, Sb, Ce, Ti, Zr, Sn, B, Cr, Fe, Al, La, Sc, Sm, Y, Ba, Mg, Sr, Zn, Cu, K. In addition to at least one of the above-mentioned chloride, fluoride, iodide, and sulfide containing element J, the anionic additive can also be selected from at least one of lithium salts containing F, Cl, I, S.

[0072] The sintering process is preferably: heating at 1 °C / min - 15 °C / min to a pre-sintering temperature of 300 °C - 800 °C, holding for within 6 h, and then heating to a sintering temperature of 800 °C - 1000 °C, holding for 6 h - 20 h and then cooling naturally.

[0073] The water washing process is preferably: quickly adding the product after sintering and crushing under the condition of stirring deionized ultrapure water, stirring for a certain time, then dehydrating and drying. Among them, the water temperature is within 25 °C, the water-to-material ratio is 0.5:1 - 5:1, the water washing time is 1 min - 10 min, the stirring speed is 100 rpm - 500 rpm, the dehydration method is selected from one of suction filtration, centrifugation, and pressure filtration, the drying method is selected from air drying or vacuum drying, the drying temperature is 100 °C - 200 °C, and the drying time is 10 h - 24 h.

[0074] Specifically, in the step of preparing the lithium iron manganese phosphate material, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium nitrate, lithium sulfate, lithium dihydrogen phosphate, lithium hydrogen phosphate, and lithium phosphate; the manganese source is selected from at least one of manganese dioxide, manganese carbonate, manganese tetroxide, manganese sesquioxide, manganese nitrate, and manganese dihydrogen phosphate; the iron source is selected from at least one of iron hydroxide, ferrous hydroxide, ferrous oxide, iron nitrate, iron phosphate, and iron sesquioxide; the phosphorus source is selected from at least one of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, manganese dihydrogen phosphate, iron phosphate, phosphoric acid, lithium hydrogen phosphate, and lithium phosphate; the additive is selected from at least one of an oxide containing element X, a hydroxide containing element X, a phosphate containing element X, and a carbonate containing element X. Element X is selected from at least one of Ti, Zr, Al, Mg, Ni, Co, Zn; the carbon source is selected from at least one of sucrose, glucose, polyethylene glycol, and citric acid.

[0075] The sintering process is preferably: heating to a pre-firing temperature of 300°C-550°C at 1°C / min-15°C / min, keeping the temperature for 2h-8h, then heating to a sintering temperature of 600°C-800°C, keeping the temperature for 6h-20h and then cooling naturally.

[0076] Specifically, in the steps of preparing lithium manganese oxide material, preparing lithium-rich and sodium-rich manganese-based material, and preparing lithium iron manganese phosphate material, the crushing device is selected from at least one of a juicer, a mechanical mill, and a jaw crusher roller.

[0077] Specifically, the mixing method of the lithium manganese oxide material and the lithium iron manganese phosphate material is selected from at least one of juicer mixing, high mixing, plowshare mixing, and ball mill mixing, preferably ball mill mixing.

[0078] Specifically, the mixing device of the lithium manganate material and the lithium-rich sodium-rich manganese-based material and the mixing device of the mixture and the lithium-rich sodium-rich manganese-based material are selected from at least one of a juicer, a high-speed mixer, and a plowshare mixer.

[0079] The present invention also provides a positive electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes the composite positive electrode material as described above. It is understandable that the positive electrode active material layer may also include materials such as a conductive agent and a binder, and the present invention does not limit this.

[0080] It should be noted that the present invention does not limit the preparation method of the positive electrode sheet, and it can be prepared using conventional processes.

[0081] The present invention also provides a battery. The battery includes the positive electrode sheet as described above. It is understandable that the battery also includes a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet, the separator and the electrolyte can adopt any conventional commercially available negative electrode sheet (or negative electrode material), the separator and the electrolyte, and the present invention is not limited to this.

[0082] The present invention further provides an electrical device, comprising the battery as described above.

[0083] It is understandable that the above-mentioned power usage settings include any equipment that uses the above-mentioned batteries, such as electric vehicles, power tools, electronic products, energy storage systems, and office equipment, but are not limited thereto.

[0084] The composite positive electrode material, positive electrode sheet and battery will be further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0085] Example 1 According to Li 1.06 Mn 1.85 La 0.05 Al 0.1 O 3.99 F 0.01 Weigh lithium carbonate and manganese tetraoxide (D 50 The mixture is mixed with lanthanum hydroxide, aluminum hydroxide and lithium fluoride, and mixed in a high-speed mixer. The mixture is loaded into a boat and put into a sintering furnace. The temperature is increased to 500°C at a rate of 3°C / min, and kept for 4 hours. The temperature is then increased to 850°C at a rate of 3°C / min, and kept for 12 hours. The temperature is then decreased to 700°C at a rate of 1°C / min, and kept for 2 hours. The mixture is cooled naturally, the sagger is taken out, the powder is crushed by a mechanical grinder, and the powder is sieved through a 325-mesh sieve to obtain the spinel lithium manganate material. Figure 1 This is a scanning electron microscope (SEM) image of the spinel lithium manganate material obtained in this embodiment. Figure 1 It can be seen that the morphology of the lithium manganese oxide material is a secondary sphere formed by the aggregation of primary particles.

[0086] According to Li 1.22 Na 0.1 (Ni 0.33 Co 0.03 Mn 0.64 ) 0.99 Nb 0.01 O 2.312 F 0.008 Weigh lithium carbonate, sodium carbonate, Ni 0.33 Co 0.03 Mn 0.64 (OH)2 precursor (D 50 The mixture is mixed with niobium pentoxide and lithium fluoride, and mixed in a high-speed mixer. The mixture is loaded into a boat and put into a sintering furnace. The mixture is heated to 600°C at a rate of 5°C / min and kept warm for 6 hours. The mixture is then heated to 900°C at a rate of 5°C / min and kept warm for 10 hours. The mixture is naturally cooled, the sagger is taken out, the mixture is mechanically ground, sieved through a 325-mesh sieve, and then washed with deionized water. The water temperature is controlled at 0°C, the water-to-material ratio is 2:1, the mixture is stirred at 400rpm, the washing time is 2min, and the mixture is filtered and dried in a vacuum oven at 120°C for 16 hours to obtain a lithium-rich and sodium-rich manganese-based material. Figure 2 The SEM image of the lithium-rich sodium-rich manganese-based material prepared in this embodiment is shown in FIG. Figure 2 It can be seen that the morphology of the lithium-rich and sodium-rich manganese-based material is a secondary sphere formed by the aggregation of primary sheets. Figure 3 The XRD pattern of the lithium-rich sodium-rich manganese-based material prepared in this embodiment is shown in FIG. Figure 3 It can be seen that there is a characteristic peak of P2 phase at a diffraction angle of 15.5°-16.5°.

[0087] The prepared spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material are mixed in a mass ratio of 7:3 to obtain a composite positive electrode material. Figure 4 This is a SEM image of the composite positive electrode material prepared in this example. Figure 5 This is a particle size distribution diagram of the composite positive electrode material prepared in this embodiment. It can be seen that the curve presents an obvious double-peak morphology.

[0088] Example 2 The difference between Example 2 and Example 1 is that the mixing mass ratio of the spinel lithium manganese oxide material to the lithium-rich sodium-rich manganese-based material is 9:1.

[0089] Example 3 The difference between Example 3 and Example 1 is that the mixing mass ratio of the spinel lithium manganese oxide material to the lithium-rich sodium-rich manganese-based material is 8:2.

[0090] Example 4 The difference between Example 4 and Example 1 is that the mixing mass ratio of the spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material is 6:4.

[0091] Example 5 The difference between Example 5 and Example 1 is that the mixing mass ratio of the spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material is 5:5.

[0092] Example 6 According to Li 1.12 Mn 1.945 La 0.05 Nb 0.005 O 3.963 F 0.037 Weigh lithium carbonate and manganese tetraoxide (D 50 The mixture is mixed with lanthanum hydroxide, niobium pentoxide and lithium fluoride, and mixed in a high-speed mixer. The mixture is loaded into a boat and put into a sintering furnace. The temperature is increased to 550°C at a rate of 5°C / min, and kept for 6 hours. The temperature is then increased to 890°C at a rate of 5°C / min, and kept for 15 hours. The temperature is then decreased to 650°C at a rate of 0.5°C / min, and kept for 4 hours. The mixture is cooled naturally, the sagger is taken out, the powder is crushed by a mechanical grinder, and the powder is sieved through a 325-mesh sieve to obtain the spinel lithium manganate material.

[0093] According to Li 1.28 Na 0.06 (Ni 0.33 Co 0.01 Mn 0.66 ) 0.98 W 0.02 O 2.295 Cl 0.045 Weigh lithium carbonate, sodium carbonate, Ni 0.33 Co 0.01 Mn0.66 (OH)2 precursor (D 50 The mixture is prepared by mixing tungsten trioxide and lithium chloride in a high-speed mixer, and then placed in a boat and put into a sintering furnace. The mixture is heated to 550°C at a rate of 4°C / min, kept warm for 4 hours, and then heated to 950°C at a rate of 4°C / min, kept warm for 14 hours, cooled naturally, taken out of the sagger, crushed by mechanical grinding, sieved through a 325-mesh sieve, and then washed with deionized water. The water temperature was controlled at 10°C, the water-to-material ratio was 3:1, stirred at 350rpm, washed for 3 minutes, filtered, and dried in a vacuum oven at 150°C for 15 hours to obtain a lithium-rich and sodium-rich manganese-based material.

[0094] The prepared spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material are mixed in a mass ratio of 7:3 to obtain a composite positive electrode material.

[0095] Example 7 According to Li 1.01 Mn 1.90 La 0.05 Ni 0.05 O 3.98 Cl 0.02 Weigh lithium carbonate and manganese tetraoxide (D 50 The mixture is prepared by mixing lanthanum hydroxide, nickel oxide and lithium chloride in a high-speed mixer, and then the mixture is put into a sintering furnace. The mixture is heated to 490°C at a rate of 5°C / min and kept warm for 5 hours. The mixture is then heated to 750°C at a rate of 5°C / min and kept warm for 10 hours. The mixture is then cooled to 680°C at a rate of 0.8°C / min and kept warm for 3 hours. The mixture is cooled naturally, the sagger is taken out, the mixture is crushed by a mechanical grinder, and the mixture is sieved through a 325-mesh sieve to obtain the spinel lithium manganate material.

[0096] According to Li 1.26 Na 0.16 (Ni 0.33 Co 0.01 Mn 0.66 ) 0.973 Sr 0.027 O 2.394 Cl 0.026 Weigh lithium carbonate, sodium carbonate, Ni 0.33 Co 0.01 Mn 0.64(OH)2 precursor, strontium oxide and lithium chloride are added to a high-speed mixer for mixing, loaded into a boat and placed in a sintering furnace. The temperature is increased to 520°C at a rate of 4°C / min and kept warm for 4 hours. The temperature is then increased to 830°C at a rate of 4°C / min and kept warm for 10 hours. The mixture is naturally cooled, taken out of the sagger, crushed with a mechanical grinder, sieved with a 325-mesh sieve, and then washed with deionized water. The water temperature is controlled at 5°C, the water-to-material ratio is 5:1, stirred at 200 rpm, washed for 8 minutes, centrifuged for dehydration, and dried in a vacuum oven at 180°C for 12 hours to obtain a lithium-rich and sodium-rich manganese-based material.

[0097] The prepared spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material are mixed in a mass ratio of 7:3 to obtain a composite positive electrode material.

[0098] Example 8 The spinel lithium manganate material prepared in Example 6 and the lithium-rich sodium-rich manganese-based material prepared in Example 7 were mixed in a mass ratio of 7:3 to obtain a composite positive electrode material.

[0099] Example 9 The lithium manganate material and the lithium-rich and sodium-rich manganese-based material were prepared by the same method as in Example 1.

[0100] According to Li 1.03 Mn 0.59 Fe 0.39 Mg 0.02 Weigh lithium carbonate, manganese tetraoxide (D 50 The powder was sintered at a rate of 5°C / min to 450°C, kept warm for 4h, and then heated to 670°C at a rate of 5°C / min, kept warm for 9h, and naturally cooled to obtain lithium manganese iron phosphate material.

[0101] Weigh 60 parts of lithium manganese oxide material and 10 parts of lithium iron manganese phosphate material, put them into a ball mill for ball milling, and obtain a mixture. Figure 6 This is a SEM image of a mixture of the lithium manganese oxide material and the lithium iron manganese phosphate material of this embodiment. It can be seen that the lithium iron manganese phosphate particles with small particle size are evenly coated on the surface of the lithium manganese oxide.

[0102] Then 30 parts of lithium-rich and sodium-rich manganese-based materials are mixed with the mixture to obtain a composite positive electrode material. Figure 7 This is the SEM image of the composite positive electrode material prepared in this embodiment. It can be seen that the lithium manganese oxide material and the lithium-rich and sodium-rich manganese-based material are alternately distributed, some extremely fine lithium iron manganese phosphate particles are coated on the surface of the lithium manganese oxide, and some particles are filled and dispersed in the gaps between the lithium manganese oxide and the lithium-rich and sodium-rich manganese-based material. Figure 8 This is a particle size distribution diagram of the composite positive electrode material prepared in this embodiment. It can be seen that the curve presents an obvious three-peak shape.

[0103] Example 10 The lithium manganate material and the lithium-rich and sodium-rich manganese-based material were prepared by the same method as in Example 1.

[0104] According to Li 1.07 Mn 0.696 Fe 0.296 Ti 0.008 PO4@1.6%C: Lithium carbonate, manganese oxide, iron phosphate, titanium dioxide and glucose were weighed, dispersed in deionized water, sand milled at 1400 rpm for 4 h, spray dried, the inlet air temperature was set to 200 °C and the outlet air temperature was set to 90 °C. The dried powder was then sintered, heated to 350 °C at a rate of 3 °C / min, kept warm for 6 h, then heated to 650 °C at a rate of 3 °C / min, kept warm for 12 h, and naturally cooled to obtain lithium manganese iron phosphate material.

[0105] Weigh 60 parts of lithium manganese oxide material and 10 parts of the above-mentioned lithium iron manganese phosphate material, put them into a ball mill and grind them to obtain a mixture. Then take 30 parts of lithium-rich sodium-rich manganese-based material and mix them with the mixture to obtain a composite positive electrode material.

[0106] Embodiment 11 The lithium manganate material and the lithium-rich and sodium-rich manganese-based material were prepared by the same method as in Example 1.

[0107] According to Li 1.01 Mn 0.782 Fe 0.182 Al 0.036 PO4@2.4%C Lithium carbonate, manganese oxide, iron phosphate, titanium dioxide and glucose were weighed, dispersed in deionized water, sand milled at 1400 rpm for 4 h, spray dried, the inlet air temperature was set to 200 °C and the outlet air temperature was set to 90 °C, and then the dried powder was sintered, heated to 350 °C at a rate of 3 °C / min, kept warm for 6 h, and then heated to 650 °C at a rate of 3 °C / min, kept warm for 12 h, and naturally cooled to obtain lithium manganese iron phosphate material.

[0108] Weigh 60 parts of lithium manganese oxide material and 10 parts of the above-mentioned lithium iron manganese phosphate material, put them into a ball mill and grind them to obtain a mixture. Then take 30 parts of lithium-rich sodium-rich manganese-based material and mix them with the mixture to obtain a composite positive electrode material.

[0109] Example 12 The difference between Example 12 and Example 9 is that 50 parts of lithium manganese oxide material and 10 parts of lithium iron manganese phosphate material are mixed and ball-milled to obtain a mixture, and then mixed with 40 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0110] Example 13 The difference between Example 13 and Example 9 is that 70 parts of lithium manganese oxide material and 10 parts of lithium iron manganese phosphate material are mixed and ball-milled as a mixture, and then mixed with 20 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0111] Embodiment 14 The difference between Example 14 and Example 9 is that 55 parts of lithium manganese oxide material and 5 parts of lithium iron manganese phosphate material are mixed and ball-milled as a mixture, and then mixed with 40 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0112] Embodiment 15 The difference between Example 15 and Example 9 is that 60 parts of lithium manganese oxide material and 20 parts of lithium iron manganese phosphate material are mixed and ball-milled to form a mixture, and then mixed with 20 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0113] Example 16 The difference between Example 16 and Example 9 is that 55 parts of lithium manganese oxide material and 25 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 20 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0114] Embodiment 17 The difference between Example 17 and Example 9 is that 58 parts of lithium manganese oxide material and 2 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 40 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0115] Embodiment 18 The difference between Example 18 and Example 9 is that 75 parts of lithium manganese oxide material and 5 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 20 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0116] Embodiment 19 The difference between Example 19 and Example 9 is that 50 parts of lithium manganese oxide material and 5 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 45 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0117] Embodiment 20 The difference between Example 20 and Example 9 is that 70 parts of lithium manganese oxide material and 15 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 15 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0118] Comparative Example 1 A lithium manganese oxide material was prepared by the same method as in Example 1, and the lithium manganese oxide material was directly used as the positive electrode material.

[0119] Comparative Example 2 A lithium-rich sodium-rich manganese-based material was prepared by referring to the same method as Example 1, and the lithium-rich sodium-rich manganese-based material was directly used as the positive electrode material.

[0120] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that according to Li 1.32 (Ni 0.33 Co 0.03 Mn 0.64 ) 0.99 Nb 0.01 O 2.312 F 0.008 Weigh lithium carbonate and Ni in proportion 0.33 Co 0.03 Mn 0.64 (OH)2 precursor, niobium pentoxide and lithium fluoride are added to a high mixer and mixed, loaded into a boat and block, put into a sintering furnace, heated to 600°C at a rate of 5°C / min, kept warm for 6 hours, then heated to 900°C at a rate of 5°C / min, kept warm for 10 hours, cooled naturally, taken out of the sagger, mechanically ground, sieved with a 325-mesh sieve to obtain a lithium-rich manganese-based material, and the spinel lithium manganese oxide material prepared in Example 1 and the lithium-rich manganese-based material are mixed in a mass ratio of 7:3 to obtain a composite positive electrode material.

[0121] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the prepared spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material are mixed in a mass ratio of 4.5:5.5 to obtain a composite positive electrode material.

[0122] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the prepared spinel lithium manganate material and the lithium-rich sodium-rich manganese-based material are mixed in a mass ratio of 9.5:0.5 to obtain a composite positive electrode material.

[0123] Comparative Example 6 The difference between Comparative Example 6 and Example 9 is that 35 parts of lithium manganese oxide material and 25 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 40 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0124] Comparative Example 7 The difference between Comparative Example 7 and Example 9 is that 48 parts of lithium manganese oxide material and 2 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 50 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0125] Comparative Example 8 The difference between Comparative Example 8 and Example 9 is that 75 parts of lithium manganese oxide material and 20 parts of lithium iron manganese phosphate material are weighed, put into a ball mill for ball milling to obtain a mixture, and then mixed with 5 parts of lithium-rich and sodium-rich manganese-based materials to obtain a composite positive electrode material.

[0126] The materials prepared in the above examples and comparative examples were subjected to physical and chemical characterization.

[0127] (1) Particle size: The particle size of the sample was tested using a laser particle size analyzer (Malvern, Master Sizer 2000). Specifically, a certain mass of sample was added to a 50 mL beaker (the amount added was based on the shading requirement), followed by sodium hexametaphosphate and about 20 mL of ultrapure water. The power was set to 120 W, the frequency to 53 Hz, and the ultrasound was performed for 5 min. After the ultrasound was completed, the particle size was tested using a MasterSizer 2000 particle size analyzer. The shading requirement was within the range of 8%-12%. The particle size test results were recorded.

[0128] (2) Specific surface area (BET): Take 5 g of sample and put it into a long tube with a bulb. First, vacuum treat it at 200°C for 2 h. Then, pass N2 for gas adsorption. The adsorption amount of adsorbate molecules (N2) by the positive electrode material sample is determined based on the pressure or weight change before and after adsorption, thereby obtaining the specific surface area.

[0129] (3) Compacted density (PD): The compacted density of the sample was tested using a particle density analyzer (CARVER4350). Specifically, the sample was loaded into a mold with a cylinder height of 28 mm and a cylinder diameter of 9 mm. The pressure was maintained at 3.5 T for a period of time, and then the pressure was reduced and maintained for a period of time. Finally, the compacted density was obtained based on the powder thickness.

[0130] The test results of the lithium manganese oxide material, lithium-rich sodium-rich manganese-based material, lithium iron manganese phosphate material prepared in the embodiment and the material prepared in the comparative example are shown in Table 1 and Table 2, and the calculation results are shown in Table 3.

[0131] Table 1 Table 2 Table 3

[0132] The test results of the positive electrode materials prepared in the above embodiments and comparative examples are shown in Table 4.

[0133] Table 4

[0134] The positive electrode materials prepared in the above embodiments and comparative examples were characterized by half-rate performance at room temperature 25°C: using N-methylpyrrolidone (NMP) as a solvent, the positive electrode material was mixed with a conductive agent (SP) and a binder (PVDF) in a ratio of 94.5wt%:3wt%:2.5wt%, and the mixture was stirred at a speed of 2000r / min for 9min to obtain a positive electrode active slurry; the slurry was evenly coated on an aluminum foil using an automatic coating machine, vacuum dried at 110°C for 30min, punched into a pole piece with a diameter of 15mm, vacuum dried at 120°C for 12h, and then assembled into a CR2430 button battery using a 1mol / L LiPF6 (solvent volume ratio EC:DMC:DEC=1:1:1) solution as an electrolyte and a metal lithium sheet as a negative electrode. The test voltage is 3.00V-4.35V, the cut-off current is 0.05C, 0.1C charge and discharge for 2 cycles (activation), 0.33C charge and discharge for 1 cycle, 1C charge and discharge for 1 cycle, 1C charge and discharge for 2 cycles, and 1C charge and discharge for 3 cycles. The test results are shown in Table 5.

[0135] Table 5

[0136] The positive electrode materials prepared in the above embodiments and comparative examples were characterized for full electrical performance of soft pack at high temperature of 45°C: using N-methylpyrrolidone (NMP) as solvent, the positive electrode material was mixed with a conductive agent (SP) and a binder (PVDF) in a ratio of 94.5wt%:3wt%:2.5wt%, and the mixture was stirred at a speed of 1500r / min for 15min to obtain a positive electrode active slurry; the slurry was evenly coated on an aluminum foil using an automatic coating machine, and the surface density was 19mg / cm 2 Then, a 1 mol / L LiPF6 (solvent volume ratio EC:DMC:DEC=1:1:1) solution was used as the electrolyte, graphite was used as the negative electrode, and the NP ratio was 1.12. A soft-pack full battery with a nominal capacity of 500 mAh was assembled to test the high-temperature cycle retention rate (100 cycles of 1C charge and discharge at 45°C), the test voltage was 2.95V-4.30V, and the cut-off current was 0.05C. The test results are shown in Table 6.

[0137] Table 6 According to Tables 4, 5 and 6, the compaction of lithium manganese oxide and lithium-rich sodium-rich manganese-based positive electrode materials is significantly improved compared to single positive electrode materials, and the cycle and rate performance can be well balanced. When lithium iron manganese phosphate is added for blending, the compaction and capacity are further improved compared to the two-doped system, and the cycle performance can be improved without affecting the rate performance, showing great application prospects.

[0138] However, in the present invention, when the ratio deviates from the specified range, the compaction and electrical properties cannot be improved at the same time or cannot be significantly improved. For example, for Comparative Example 3, although the compaction is as high as 3.03 g / cm 3 , but the capacity is not improved, and the rate and cycle are poor; for comparative example 4, the capacity and cycle are ideal, but the rate is poor and the compaction is low (the situation of comparative example 6 is the same); for comparative example 5, the rate performance is good, but the compaction is extremely low, and the capacity and cycle are also poor. I will not give examples one by one here. In summary, in order to obtain a composite positive electrode material with excellent comprehensive performance, it is necessary to blend according to the ratio provided by the present invention.

[0139] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0140] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A composite positive electrode material, characterized in that: The composite cathode material includes lithium manganate material and lithium-rich and sodium-rich manganese-based material, and the median particle size of the lithium manganate material is greater than that of the lithium-rich and sodium-rich manganese-based material; The tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2) < PD < 1.2×(X1×PD1 + X2×PD2), and PD > 1.02×max{PD1, PD2}, where X1 represents the mass fraction of the lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 90%, PD1 represents the tap density of the lithium manganate material, X2 represents the mass fraction of the lithium-rich and sodium-rich manganese-based material in the composite cathode material, 10% ≤ X2 ≤ 50%, PD2 represents the tap density of the lithium-rich and sodium-rich manganese-based material, and max represents taking the maximum value of PD1 and PD2.

2. The composite positive electrode material according to claim 1, characterized in that The particle size distribution width SPAN of the composite cathode material satisfies: SPAN ≥ 1.3×(SPAN1 + SPAN2) / 2, where SPAN1 represents the particle size distribution width of the lithium manganate material, and SPAN2 represents the particle size distribution width of the lithium-rich and sodium-rich manganese-based material.

3. The composite positive electrode material according to claim 1, characterized in that: The difference between the median particle size of the lithium manganate material and that of the lithium-rich and sodium-rich manganese-based material is 5 μm - 15 μm.

4. The composite positive electrode material according to claim 1, characterized in that The lithium manganate material satisfies at least one of the following conditions: (1)8μm≤D 50 ≤20μm; (2)3μm≤D 10 ≤7μm; (3) The particle size distribution width SPAN1 of the lithium manganate material is 1 - 2; (4) The compaction density PD1 of lithium manganese oxide material is 2.6g / cm 3 -2.9g / cm 3 ; (5) The specific surface area of ​​lithium manganese oxide material is 0.2m 2 / g-0.8m 2 / g; (6) The lithium manganate material has a spinel crystal structure; (7) The chemical formula of the lithium manganate material is Li 1+x Mn 2-a A a O4D b , where 0 ≤ x ≤ 0.2, 0 < a ≤ 0.2, 0 ≤ b ≤ 0.05, A represents a cation doping element, and A is selected from at least one of W, Mo, V, Ta, Nb, P, Zr, Ti, Cr, Al, Fe, La, Ce, Nd, Sm, Gd, Tm, Bi, Co, Mg, Ni, Zn; D represents an anion doping element, and D is selected from at least one of F, Cl, I, S.

5. The composite positive electrode material according to claim 1, characterized in that: The lithium-rich and sodium-rich manganese-based material satisfies at least one of the following conditions: (1)3μm≤D 50 ≤6μm; (2)1μm≤D 10 ≤4μm; (3) The particle size distribution width SPAN2 of the lithium-rich and sodium-rich manganese-based material is 0.5 - 1.5; (4) The compaction density PD2 of lithium-rich and sodium-rich manganese-based materials is 2.7 g / cm 3 -2.9g / cm 3 ; (5) The specific surface area of ​​lithium-rich and sodium-rich manganese-based materials is 1m 2 / g-4m 2 / g; (6) The lithium-rich and sodium-rich manganese-based material has a layered structure; (7) In the X-ray diffraction pattern of lithium-rich and sodium-rich manganese-based materials, the diffraction peak intensities of (002), (003), (104), and (101) are denoted as I (002) ,I (003) ,I (104) ,I (101) , 0.01≤I (002) / [I (003) +I (104) +I (101) ]≤0.5; (8) The chemical formula of the lithium-rich and sodium-rich manganese-based material is Li 1+m Na n Ni 1-c-d-e Co c Mn d M e O f E g , where 0 ≤ m ≤ 0.3, 0.05 ≤ n ≤ 0.3, and 0.1 ≤ m + n ≤ 0.5, 0.2 ≤ 1 - c - d - e ≤ 0.4, 0 ≤ c ≤ 0.1, 0.5 ≤ d ≤ 0.8, 0 < e ≤ 0.05, 0 ≤ g ≤ 0.1, and f + g = 2 + m + n. M represents a cation doping element, and M is selected from at least one of W, Mo, Nb, Ta, V, Te, Sb, Ce, Ti, Zr, Sn, B, Cr, Fe, Al, La, Sc, Sm, Y, Ba, Mg, Sr, Zn, Cu, K. E represents an anion doping element, and E is selected from at least one of F, Cl, I, S.

6. The composite positive electrode material according to claim 1, characterized in that: The composite cathode material further includes lithium iron manganese phosphate material, and the median particle size of the lithium-rich and sodium-rich manganese-based material is greater than that of the lithium iron manganese phosphate material; The tap density PD of the composite cathode material satisfies: 1.05×(X1×PD1 + X2×PD2 + X3×PD3) < PD < 1.2×(X1×PD1 + X2×PD2 + X3×PD3), and PD > 1.02×max{PD1, PD2, PD3}, where X1 represents the mass fraction of the lithium manganate material in the composite cathode material, 50% ≤ X1 ≤ 70%, PD1 represents the tap density of the lithium manganate material, X2 represents the mass fraction of the lithium-rich and sodium-rich manganese-based material in the composite cathode material, 20% ≤ X2 ≤ 40%, PD2 represents the tap density of the lithium-rich and sodium-rich manganese-based material, X3 represents the mass fraction of the lithium iron manganese phosphate material in the composite cathode material, 5% ≤ X3 ≤ 20%, PD3 represents the tap density of the lithium iron manganese phosphate material, and max represents taking the maximum value of PD1, PD2, and PD3.

7. The composite positive electrode material according to claim 6, characterized in that: The particle size distribution width SPAN of the composite cathode material satisfies: SPAN ≥ 1.3×(SPAN1 + SPAN2 + SPAN3) / 3, where SPAN1 represents the particle size distribution width of the lithium manganate material, SPAN2 represents the particle size distribution width of the lithium-rich and sodium-rich manganese-based material, and SPAN3 represents the particle size distribution width of the lithium iron manganese phosphate material.

8. The composite positive electrode material according to claim 6, characterized in that: The difference between the median particle size of the lithium-rich and sodium-rich manganese-based material and the median particle size of the lithium iron manganese phosphate material is 2 μm-5 μm.

9. The composite positive electrode material according to claim 6, characterized in that: The lithium manganese iron phosphate material meets at least one of the following conditions: (1)0.5μm≤D 50 ≤2μm; (2)0.1μm≤D 10 ≤1μm; (3) The particle size distribution width SPAN3 of lithium manganese iron phosphate material is 1.0-3.0; (4) The compaction density PD3 of lithium manganese iron phosphate material is 2.0g / cm 3 -2.5g / cm 3 ; (5) The specific surface area of ​​lithium manganese iron phosphate material is 15m 2 / g-25m 2 / g; (6) Lithium manganese iron phosphate material has an olivine crystal structure; (7)The chemical formula of the lithium manganese iron phosphate material is Li 1+y Mn p Fe q Q 1-p-q PO4@C, where 0 ≤ y ≤ 0.1, 0.4 ≤ p < 1, 0 < q ≤ 0.6, 0 ≤ 1 - p - q ≤ 0.05, and Q is selected from at least one of V, Nb, Ti, Zr, Al, Mg, Ni, Co, and Zn.

10. The composite positive electrode material according to any one of claims 1 to 9, characterized in that: The composite positive electrode material satisfies at least one of the following conditions: (1)3μm≤D 50 ≤15μm; (2)1μm≤D 10 ≤4μm; (3) The particle size distribution width SPAN of the composite positive electrode material is ≥ 2.0; (4) The compaction density of the composite positive electrode material is PD ≥ 2.9 g / cm 3 ; (5) The specific surface area of ​​the composite positive electrode material is 0.5m 2 / g-6m 2 / g.

11. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer comprises the composite positive electrode material according to any one of claims 1 to 10.

12. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.

Citation Information

Patent Citations

  • Modified lithium-rich manganese-based oxide positive electrode material and preparation method thereof

    CN110797527A

  • Novel double-doped mixed cobalt-free system positive plate and lithium ion battery

    CN113611838A

  • Pole piece, electrochemical device and electronic device

    CN113646933A

  • High-nickel positive electrode material and preparation method thereof

    CN114678524A

  • Positive plate and preparation method thereof, electrode assembly, energy storage equipment and electric equipment

    CN115832224A

Cited By

  • Composite positive electrode material, positive electrode sheet and battery

    WO2026145689A1